IMPLEMENTASI MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN MURID TERHADAP MATERI TOLERANSI PADA PELAJARAN PAI KELAS VIII DI SMPN 2 KARAWANG BARAT - Karmila, Rahma Ayu; Subagja, Robie Wahab; Annisa, Siti; Setiani, Uni; Tauhidah, Vicka; Khulasoh, Siti (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to improve the understanding of tolerance material among eighth-grade students at SMPN 2 Karawang Barat through the implementation of the Problem Based Learning (PBL) method. The background of this research is the low learning outcomes of students in the Pancasila Education subject, particularly in the topic of tolerance. The study employs a Classroom Action Research (CAR) approach, conducted in two cycles. The research subjects consisted of 38 eighth-grade students at SMPN 2 Karawang Barat. Data were collected through multiple-choice tests and analyzed using descriptive quantitative methods. The study is considered successful if at least 75% of students achieve a score of 75 or above. The results indicate that the Problem Based Learning (PBL) method is effective in enhancing students' understanding of tolerance material.